Distribution and antibiotic susceptibility profiles of Aeromonas spp. from different aquatic environments in north Lebanon - Rayane Rafei; Imad Al Kassaa; Marwan Osman; Fouad Dabboussi; Monzer Hamze (Journal of Infection in Developing Countries)
Introduction: Bacteria of Aeromonas genus are ubiquitous organisms in aquatic environments. This work aims to explore the presence of four clinically relevant species in Lebanese waters and to study their susceptibility to antibiotics.